The ethics of marketing in Colombia a look from some experts of the academy - Londoño-Cardozo, José; Tello-Castrillón , Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper is aimed to identify the implicit ethics in marketing in Colombia according to many expert professors’ perspectives from the best Colombian universities. The methodological design used was the hermeneutic analysis of the information gathered through semi-directed interviews. The results show that the ethics taught in Colombian undergraduate programs has a hegemonic moral position based on utilitarian ethics, which is important for the professionals of marketing and comes from religious morality. It is also taught through ethical codes and tends to be a cross subject in curricula. Although several universities try to incorporate the ethical issues throughout their curricula, other universities have eliminated this component or have left the learning of this component as a student's choice. The ethics approach taught in undergraduate marketing programs in Colombia should be reviewed to avoid phenomena in the national context that are considered inappropriate, such as unfair competition or misleading advertising.